The other passenger - Candlish, Louise (Atria Paperback, 2021)
"It all happens so quickly. One day you're living the dream, commuting to work by ferry with your charismatic neighbor Kit in the seat beside you. The next, Kit hasn't turned up for the boat and his wife, Melia, has reported him missing. When you get off at your stop, the police are waiting. Another passenger saw you and Kit arguing on the boat home the night before and the police say that you had a reason to want him dead. You protest. You and Kit are friends--ask Melia, she'll vouch for you. And who exactly is this other passenger pointing the finger? What do they know about your lives? No, whatever danger followed you home last night, you are innocent, totally innocent."--Amazon.